2015
DOI: 10.1162/jocn_a_00702
|View full text |Cite
|
Sign up to set email alerts
|

Neural Emotion Regulation Circuitry Underlying Anxiolytic Effects of Perceived Control over Pain

Abstract: Anxiolytic effects of perceived control have been observed across species. In humans, neuroimaging studies have suggested that perceived control and cognitive reappraisal reduce negative affect through similar mechanisms. An important limitation of extant neuroimaging studies of perceived control in terms of directly testing this hypothesis, however, is the use of within subjects-designs, which confound participants' affective response to controllable and uncontrollable stress. To compare neural and affective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 52 publications
5
48
1
Order By: Relevance
“…Although the link between childhood trauma and positive symptoms of somatoform dissociation (e.g. medically unexplained pain) was tenuous in the current study, there is evidence that childhood trauma is associated with physical as well as emotional pain (Nelson, Cunningham, & Kashikar-Zuck, 2017; Sachs-Ericsson, Sheffler, Stanley, Piazza, & Preacher, 2017) and that perceived control over pain is associated with reduced anxiety and enhanced emotion regulation (Salomons, Nusslock, Detloff, Johnstone, & Davidson, 2015). Therefore, assessment of somatoform dissociation appears warranted as a precaution when clinically treating adults with CPTSD/DESNOS.…”
Section: Discussionmentioning
confidence: 50%
“…Although the link between childhood trauma and positive symptoms of somatoform dissociation (e.g. medically unexplained pain) was tenuous in the current study, there is evidence that childhood trauma is associated with physical as well as emotional pain (Nelson, Cunningham, & Kashikar-Zuck, 2017; Sachs-Ericsson, Sheffler, Stanley, Piazza, & Preacher, 2017) and that perceived control over pain is associated with reduced anxiety and enhanced emotion regulation (Salomons, Nusslock, Detloff, Johnstone, & Davidson, 2015). Therefore, assessment of somatoform dissociation appears warranted as a precaution when clinically treating adults with CPTSD/DESNOS.…”
Section: Discussionmentioning
confidence: 50%
“…The fact that attention and controllability reliably modulate pain (Eccleston and Crombez, 1999;Wiech et al, 2006;Yoshida et al, 2013;Salomons et al, 2007Salomons et al, , 2015Taylor et al, 2017;Br€ ascher et al, 2016), beyond that which can be explained by mechanisms above, suggests that factors intrinsic to learning and control specifically modulate pain. Although the goal of RL is to learn to minimize pain as an objective function, performance can be enhanced by intrinsically modulating pain according to its informational value in learning.…”
Section: Modulation By Informational Valuementioning
confidence: 99%
“…Among chronic pain patients, maladaptive emotion regulation strategies like emotion suppression have been shown to exacerbate pain under stressful conditions (Burns 2006) by increasing physiological reactivity to pain and stress (Burns et al 2011). Neuroimaging research has suggested that the regulation of pain and emotion share overlapping neural substrates, including cortico-limbic-striatal circuits (Salomons et al 2014) which partially overlap with the central autonomic network thought to govern HRV. These studies suggest a linkage between emotion regulatory capacity and pain, yet it is unclear whether chronic pain patients who use and misuse opioids evidence emotion regulation deficits.…”
Section: Introductionmentioning
confidence: 99%